Commentaire sur les Catégories. - Simplicius, of Cilicia. (Philosophia Antiqua, 1990)
The French translation with commentary, the first in a modern language, allows historians of philosophy access to a fundamental work for the understanding of medieval and modern thought. They could also explore more easily the great variety of information contained in the commentary of Simplicius on the history of the exegis of the Catégories of Aristotle , and more generally on the history of comparative philosophy of Simplicius. They will discover some important aspects in the actual thought of Simplicius, which so far has hardly been explored.